2014
DOI: 10.25289/ml.2014.3.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Transmeatal Low Level Laser Therapy (LLLT) on Vestibular Inner Ear after Topical Gentamicin Ototoxicity

Abstract: Background and ObjectivesThe objectives of this study is to evaluate any adverse effects on outer and inner ear structures after transmeatal low level laser therapy (LLLT) and to see the effects of transmeatal LLLT on gentamicin induced unilateral vestibulopathy in guinea pigs. Materials and MethodsWe measured penetration rate of transmeatal low level laser (LLL) into the perilymphatic space of cochlea through a tympanic membrane, cochlea wall and hearing level post transmeatal LLLT were measured. Histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies have reported that LLLT is effective in various fields, including treatment of alopecia, 16 vestibulopathy, 17 and ophthalmic diseases. 18,19 However, the mechanism of LLLT has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that LLLT is effective in various fields, including treatment of alopecia, 16 vestibulopathy, 17 and ophthalmic diseases. 18,19 However, the mechanism of LLLT has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%